Perubahan Sosial pada Masyarakat Papua selama Penyelesaian Konflik Papua oleh Pemerintah Indonesia - Masri, Ilman Syarif (As- Sakinah Law Firm & Society of Visual Informatics, 2024)
Papua is one of the regions located in the eastern part of Indonesia with topographical conditions that are difficult for the government to implement development smoothly. This has led to prolonged conflict due to dissatisfaction with the ruling government. The solutions offered by the government are solutions to improve welfare and development in the Papua region as well as legal regulations to make Papua an area with special autonomy. The solution has an impact on the social life of the Papuan people, so this research aims to explain social change in conflict resolution by the Indonesian government. This research uses descriptive qualitative research methods with data collection using document studies and literature reviews related to the Papua conflict, the socio-cultural conditions of the Papuan people and the impact of conflict and conflict resolution on the Papuan people. This study found that the impact of the conflict has changed the social life of the Papuan people where the Papuan people have experienced a decrease in welfare and education aspects, including the emergence of distrust of the government and suspicion of migrants. However, the impact of conflict can increase sensitivity to politics and human rights in Papuan society.